Pemberdayaan Masyarakat dalam Pemanfaatan Lahan Kolam Lele sebagai Upaya Pencegahan Stunting - Aryani, Ni Putu; Afrida, Baic Ricca; Idyawati, Susilia; Jannati, Sri Hawari (Universitas Baiturrahim, 2024)
Nutritional problem that still often occurs in toddlers is stunting. The prevalence of stunting in NTB was recorded at 33.5%, still above the national figure of 29.6%. Empower the community to use catfish pond land as an effort to prevent stunting. Implementation methods include preparation, implementation and evaluation. The preparation stage involved obtaining permits from institutions and the local government. The implementation stage involved providing material about using land as a catfish pond to prevent stunting to 30 heads of families. In the evaluation of activities, there was an increase in knowledge about handling stunting and how to prevent it by using catfish pond land as an effort. Conclusion: Together with the village government, the community will try to utilize the yard as a way to prevent stunting in toddlers